Multisystem Resilience in Disaster Volunteers: A Review of the Literature - Dewi, Yuli Arinta; Soeparno, Koentjoro; Pertiwi, Pradytia Putri; Fuady, Mizan Bustanul (Jurnal Psikologi, 2025)
There is a growing interest in multisystem resilience within disaster studies; however, the resilience of disaster volunteers remains an underexplored area. This review aims to bridge this gap by analyzing existing studies that examine how internal and external systems influence the psychological resilience of disaster volunteers. Specifically, it addresses the question: How is multisystem resilience conceptualized and supported among disaster volunteers in the existing literature? We applied a narrative review approach and retrieved literature from the Scopus database, covering all available publication years. The analysis was supported by thematic coding using ATLAS.ti software to identify and extract key themes from the selected studies. Out of 602 articles and proceedings screened, only 11 met our inclusion criteria. Findings indicate that, compared to other forms of civic engagement, disaster volunteering is more likely to involve physical and mental health risks. At the same time, it provides opportunities to strengthen well-being and resilience. This review highlights the importance of a multisystem resilience perspective, emphasizing the dynamic interaction between internal and external systems in fostering the resilience of disaster volunteers.